Plasma concentrations of C-nartiuretic peptide and endothelin-1 in women with essential hypertension which suffered vascular complication when inherent of different variants of angiotensin II type 1 receptor gene - S. V. Franchuk; O. L. Starzhynska (Zaporožskij Medicinskij Žurnal)
Plasma level of C-natriuretic peptide (CNP) and endothelin-1 (ET-1) was performed among postmenopausal age’s women, patients with essential hypertension (EH), which complicated myocardial infarction or cerebral stroke, who live in Vinnitsa region, with inherent of different variants of angiotensin II type 1 receptor gene. Genotyping gene AT1R was carried out using polymerase chain reaction (PCR) after selecting of genomic DNA from leucocytes of the venous blood. For determination the concentration of CNP and ET-1in plasma of the patients the ELISA method was used. It is shown that plasma level CNP and ET-1is reliable higher in patients of all groups with AC and CC genotypes, compared with AA genotype (р<0,05). Carrying C allele of AT1R gene has ability to correlate with higher plasma concentration of the CNP and ET. Because CNP and ET-1 are antagonists the CNP/ET-1 coefficient (ratio plasma level CNP and ET-1) was calculated in each investigated group. CNP/ET-1 coefficient is responsible for relationship between vasodelatators and vasoconstrictors. In all patients with EH CNP/ET-1 coefficient was lower than in control group, it means that vasoconstrictors prevail over vasodelatators. In the same time in patients with C allele of AT1R gene CNP/ET-1 coefficient was higher than in patients with AA genotype, which possible is result of increasing compensator mechanisms.